Effectiveness of Flax Seed Pillow on Stress and Physical Parameters of Premature Infants (Medico Legal Update, 2020)
Introduction : As per WHO report in 2018, every year, 15 million babies are born prematurely, the leadingcause of child deaths under age five every year. Many survivors of preterm birth face a lifetime of disability,including learning disabilities and visual and hearing problems.Purpose of the study: To find the effectiveness of a flaxseed pillow on stress and physical parameters inpremature infants.Methodology : An evaluative two group pretest post-test approach selected for the study. Premature infantsselected by a purposive sampling technique and applied with a flaxseed pillow. All the infants were observedtwo times per day for five consecutive days from the day of recruitment. Stress and Physical parametersobtained and analyzed to find the effectiveness of the intervention.Results: Out of 34 Premature infants, 17 (50%) underwent flax seed pillow treatment, and remaining werethe control group. Independent sample t-test results showed that there is a significant difference (pre-post) inthe stress score between the experimental and control group. The paired t-test result revealed that there is adifference (p< 0.05) in the stress score among the experimental groups for all five days.Conclusion: An increasing number of premature birth is one of the most significant issues faced by thecountry today. Many developmental care interventions provided to preterm babies, which are cost-effectivecare and help these vulnerable in their phase of prematurity. Flaxseed pillow was effective in reducing thestress of premature infants in the NICU.